The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1021/nn100272q
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Gold@Gold(I)−Thiomalate Core@Shell Nanoparticles

Abstract: In this paper, the synthesis of gold at gold(I)-thiolate core at shell nanoparticles is described for the first time. The chemical nature and structure of these nanoparticles were characterized by a multi-technique approach. The prepared particles consist of gold metallic cores, about 1 nm in size, surrounded by stable gold(I)-thiomalate shells (Au at Au(I)-TM). These nanoparticles could be useful in medicine due to the interesting properties that gold(I)-thiomalate has against rheumatoid arthritis. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
54
4
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 71 publications
9
54
4
1
Order By: Relevance
“…In Figure 4.1, a conventional high-resolution transmission electron microscopy (HR-TEM) micrograph of a bimetallic nanoparticle 2 nm in diameter shows the interatomic distances; however, the contrast is not directly related with the different atomic positions in the bimetallic nanoparticle (Corthey et al, 2010) proposed by the theoretical model shown in Figure 4.1b. …”
Section: Stem and Temmentioning
confidence: 99%
See 1 more Smart Citation
“…In Figure 4.1, a conventional high-resolution transmission electron microscopy (HR-TEM) micrograph of a bimetallic nanoparticle 2 nm in diameter shows the interatomic distances; however, the contrast is not directly related with the different atomic positions in the bimetallic nanoparticle (Corthey et al, 2010) proposed by the theoretical model shown in Figure 4.1b. …”
Section: Stem and Temmentioning
confidence: 99%
“…When nanoparticles are being prepared for analysis by TEM or STEM, it is common to prepare the specimen by placing the nanoparticles on holey carbon copper grids. In some synthesis procedures, the nanoparticles are covered with a layer of organic ligands (Corthey et al, 2010); if required, this organic layer can be removed by exposing the specimen to a beam shower for a few minutes before placing it in the microscope.…”
Section: The Principles Of Tem and Stem Imagingmentioning
confidence: 99%
“…Metallic nanoparticles include iron-oxide nanoparticles, silica-gold nanoshells, gold nanoparticles, and Quantum dots (cadmium, selenium, and zinc) (Riehemann et al, 2009;van Vlerken & Amiji, 2006). Although originally developed for cancer treatment, these technologies are currently being translated to rheumatoid arthritis treatment applications (Corthey et al, 2010). The use of metals can yield multifunctional nanoparticles whereby both therapeutic delivery and imaging are facilitated (Riehemann et al, 2009).…”
Section: Nanoparticulate Carrier Systemsmentioning
confidence: 99%
“…However, the synthesis of gold core-gold(I)-thiomalate nanoparticles (Au@AU(I)-TM) was recently completed. Au@Au(I)-TM bears surface carboxylate groups which may be further modified for specific drug delivery applications (Corthey et al, 2010); therefore, these nanoparticles may pave the way to a renewed interest in the use of gold in the treatment of rheumatoid arthritis.…”
Section: Nanoparticle Carrier Systems For Rheumatoid Arthritis Treatmentmentioning
confidence: 99%
“…203,204 In X-ray diffraction (XRD), 140 X-ray beams are projected over the NPs in a determined angle, called theta "θ", and the diffracted X-rays are collected in an angle of 2θ (See Table 5). XRD allows structural phase identification of the NPs cristallinity (e.g., between magnetite and maghemite NPs) 115,116 giving also the average particle size by using the Scherrer equation.…”
mentioning
confidence: 99%